EFFECTIVE USE OF ATM WITH SECURITY - Kumar, Shiv; shrama, Shrawan kumar; kumar, Awanit (IJRDO -Journal of Computer Science Engineering, 2015)
ATM (automated teller machine) is a new generation banking system. ATM is most usable friendly machine. The main objective of this paper is to enhance more Security to ATM users’ as criminal offence occurs more due to miss use of ATM. Since ATM have lack of Security we have interoduced few obtion to reduce risk and miss use of ATM card by developing Thumb impression Security option without any need of hardware just only by upgrading software and second obtion is to changing the criteria of limits of cash withdrawal and the third proposal is to make ATM Eco-friendly i.e. cash deposit can be make by ATM only this will reduce the rush and save the Bankers’ time and no need to fill form for cash deposition it will save paper.